Revitalization Model of Medan City Based Home Shop as an Image-Forming Identity City - Deni Saadah Purba; Dwi Lindarto Hadinugroho (Talenta Publisher, 2020)
The Shophouse is a multi-story building that has multiple functions. The 1st floor is used as a commercial area, and the 2nd floor above is used as a residential place. Revitalization is an effort to revive an urban area through improving the quality of the environment, taking into accounts the socio- cultural aspects and characteristics of the region. The facade is the identity of the building itself by retaining elements and elements on the building façade. This research purposes of finding the dominant appearance of the elements of finding in the shophouse façade in the city of Medan, which is useful for the design revitalizing model of the face of the city as the image of the identity city. The method used in this study is qualitative descriptive, with a variable observation phase with the collection of primary and secondary data through direct observation in the field, then analyzed the shop facade elements that have been Grouped and found the most dominant element. The result of the analysis of the dominant facade element found in the shop façade of Medan is China, Malay, and India. The findings of the dominant facade element can be the identity identifier of the region and city of Medan today.